HUBUNGAN PENGGUNAAN KONTRASEPSI HORMONAL DENGAN KEJADIAN HIPERTENSI PADA WANITA USIA REPRODUKTIF (15-49 TAHUN) DI WILAYAH KERJA PUSKESMAS TELADAN KOTA MEDAN TAHUN 2019 - Risda Mariana Manik; Bernadetta Ambarita (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2020)
Background: The prevalence of hypertension in Indonesia continues to increase, especially in women. The incidence rate reached 28.8% higher than the incidence of hypertension in men which is 22.8%. There are factors that make women more at risk of hypertension than men. Namely the use of hormonal contraception in women whose users reach 47.54%. Purpose: to analysis Correlational hormonal contraceptive use and hypertension. Methods: This research is an observational survey research, case-control design. Held in the Work Area of the Medan City Primary Health Center. Conducted from March-June 2019. The population were all women of productive age (15-49 years) totaling 572 people. The size of the case sample was 35 people and 35 controls. Case samples were taken by means of consecutive sampling, control samples were taken by convenient sampling. Data analysis was performed univariately and bivariately using the Chi Square statistical test (?2) with a significance level of 0.05. Results: In the hypertension group, 77.1% used hormonal contraception and 22.9% did not use hormonal contraception. Whereas in the non hypertensive group 62.9% did not use hormonal contraception only 37.1% used hormonal contraception. There is a relationship between hormonal contraceptive use and hypertension in women of reproductive age. A value (OR = 5.7; 95% CI 2,008-16,244) means that women of reproductive age are at risk of experiencing hypertension 5.7 times greater if women of reproductive age use hormonal contraception than those who do not use hormonal contraception. Conclusion: Women of reproductive age are at risk of developing hypertension when using hormonal contraception. Therefore, it is recommended that women of reproductive age prefer non-hormonal contraception or natural contraception. If using hormonal contraception to keep monitoring blood pressure regularly at least 3 months after using hormonal contraception and immediately stop using hormonal contraception if there is a hypertensionKeyword: Hormonal contraception; Hypertension; Women at Reproductive age